2021
DOI: 10.1021/acs.inorgchem.1c00339
|View full text |Cite
|
Sign up to set email alerts
|

Remote Substituents as Potential Control Elements for the Solid-State Structures of Hypervalent Iodine(III) Compounds

Abstract: Hypervalent iodine (HVI) compounds are very important selective oxidants often employed in organic syntheses. Most HVI compounds are strongly associated in the solid state involving interactions between the electropositive iodine centers and nearby electron lone pairs of electronegative atoms. This study examines the impact of remote substituents on select families of HVI compounds as means to achieve predictable two-dimensional extended solid-state materials. Crystallographic analyses of 10 HVI compounds from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…More recently, hypervalent iodine compounds containing multiple iodine­(III) centers have drawn interest for applications as material precursors, supramolecular materials, and bidentate Lewis acids. , Stang and co-workers have reported a series of macrocyclic aryliodoniums in which multiple iodine­(III) atoms bridge the biaryl together, for example, compounds 29 and 30 , (Scheme A). These macrocyclic aryliodoniums are more like acyclic.…”
Section: Advance In Design and Synthesis Of Cyclic Aryliodoniumsmentioning
confidence: 99%
“…More recently, hypervalent iodine compounds containing multiple iodine­(III) centers have drawn interest for applications as material precursors, supramolecular materials, and bidentate Lewis acids. , Stang and co-workers have reported a series of macrocyclic aryliodoniums in which multiple iodine­(III) atoms bridge the biaryl together, for example, compounds 29 and 30 , (Scheme A). These macrocyclic aryliodoniums are more like acyclic.…”
Section: Advance In Design and Synthesis Of Cyclic Aryliodoniumsmentioning
confidence: 99%
“…The supramolecular architectures most frequently adopted by I III -based species have been highlighted in reviews and book considerations. Diaryliodonium salts (a subclass of λ 3 -iodanes) function as double-σ-hole donors and comprise a class of promising tectons for the preparation of novel supramolecular arrays exhibiting useful functional properties, e.g., of halogen bonded organic frameworks (the so-called XOFs) with permanent porosity. , Analysis of the Cambridge Structural Database (CSD) revealed that heterotetrameric adducts (0D architectures) are the most common supramolecular arrangement formed by diaryliodonium salts regardless of the used anion, while 1D chains are much less abundant arrays (Figure A,C).…”
Section: Introductionmentioning
confidence: 99%
“…25 We have recently reported on crystal structural analyses of para-donor-substituted ArI(OAc)2 and their associated intra-and inter-molecular I•••O interactions, with the goal of rationally designed supramolecular materials. 26 These studies revealed that intramolecular I•••O interactions from the vicinal carbonyl oxygen atoms of the carboxylate groups tended to block access to the iodine(III) centers from prospective electron rich donor groups of neighboring molecules. Cyclic iodonium ylides thus offered the opportunity to examine HVI compounds free of interference of the directly bound carboxylate groups.…”
Section: Introductionmentioning
confidence: 99%